1997
DOI: 10.1111/j.2042-7158.1997.tb06790.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mammalian Intestinal Bacteria in the Reductive Metabolism of Zonisamide

Abstract: Zonisamide (1,2-benzisoxazole-3-methanesulphonamide), a new anticonvulsant, is mainly metabolized to 2-sulphamoylacetylphenol by reduction of the benzisoxazole ring. Recent studies have shown that mammalian liver enzymes are responsible for the reduction of zonisamide. Because intestinal bacteria can also mediate the reduction of xenobiotics, this study was designed to evaluate the role of intestinal bacteria in in-vivo reductive metabolism of zonisamide. Treatment of rats with antibiotics significantly reduce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
47
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 80 publications
(48 citation statements)
references
References 8 publications
1
47
0
Order By: Relevance
“…The 1,2-benzisoxazole N-O cleavage product of ZNS, 2-sulphamolacetylphenol (SM-AP; m/z: 215) is one of the major metabolites [6,7]. Reduction of ZNS to SMAP is mediated by cytochrome P450 [7,8] and by mammalian intestinal bacteria in vivo [9]. OH.…”
Section: Resultsmentioning
confidence: 99%
“…The 1,2-benzisoxazole N-O cleavage product of ZNS, 2-sulphamolacetylphenol (SM-AP; m/z: 215) is one of the major metabolites [6,7]. Reduction of ZNS to SMAP is mediated by cytochrome P450 [7,8] and by mammalian intestinal bacteria in vivo [9]. OH.…”
Section: Resultsmentioning
confidence: 99%
“…However, it is not clear at this time to what extent hepatic cytochrome P450 enzymes are contributing to the N-dearylation of 3-(indol-1-yl)-1,2-benzisoxazoles observed in vivo in the rat. Other biological systems, such as aldehyde oxidase or gut microflora, that are able to catalyze the reduction of 1,2-isoxazole, as has been demonstrated for zonisamide (Sugihara et al, 1996;Kitamura et al, 1997), could be involved as well.…”
Section: Discussionmentioning
confidence: 99%
“…In the rat, 2-(sulfamoylacetyl)-phenol glucuronide and 2-(1-aminosulfamoylethyl)-phenol, two metabolites identified in rat urine, were most likely formed from a common imine intermediate that resulted from N-O bond cleavage (Stiff and Zemaitis, 1990). It was subsequently shown that metabolism of zonisamide to 2-(sulfamoylacetyl)-phenol was mediated by rat liver microsomes (Nakasa et al, 1992;Stiff et al, 1992) and, to a lesser extent, cytosolic (Sugihara et al, 1996) and intestinal extracts (Kitamura et al, 1997). The microsomal reduction of zonisamide was NADPH-dependent and was inhibited by carbon monoxide and cimetidine, suggesting that the reaction was cytochrome P450-mediated.…”
mentioning
confidence: 99%
“…This method has the advantage of capturing a greater diversity of organisms and has been successfully applied to identify numerous drugs that are susceptible to microbial metabolism (Valerino et al, 1972;Caldwell and Hawksworth, 1973;Smith and Griffiths, 1974;Powis et al, 1979;Koch and Goldman, 1979;Koch et al, 1980;Lindenbaum et al, 1981;Elmer and Remmel, 1984;Harris et al, 1986;Strong et al, 1987;Shu et al, 1991;DH Kim et al, 1992;Lavrijsen et al, 1995;Watanabe et al, 1995;Kitamura et al, 1997;Sasaki et al, 1997;Basit and Lacey, 2001;Basit et al, 2002;Deng et al, 2011;Li et al, 2012;McCabe et al, 2015). However, when testing a community of microorganisms collectively, inter-strain antagonism may mask This article has not been copyedited and formatted.…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%
“…For example, the selection of a single representative strain of Escherichia coli such as K-12 would sample just 19% of the known genetic diversity in the species: ~4,400 genes out of the 23,107 observed across the E. coli pan-genome (Ding et al, 2018). Nonetheless, this approach has been successful in identifying multiple drug-metabolizing bacterial species (Peppercorn and Goldman, 1972;Caldwell and Hawksworth, 1973;Saha et al, 1983;Strong et al, 1987;Hattori et al, 1988;Shu et al, 1991;Rafii et al, 1997;Kitamura et al, 1997;Shelton et al, 1997).…”
Section: Mastering Microbial Metabolismmentioning
confidence: 99%